P223 Adaptability and reproducibility of a memory disruption rTMS protocol in the PharmaCog IMI European project. Issue 3 (March 2017) - Martin, P.; Lanteaume, L.; Solana, E.; Casse-Perrot, C.; Fernández-Cabello, S.; Babiloni, C.; Marzano, N.; Junqué, C.; Rossini, P.M.; Micallef, J.; Truillet, R.; Charles, E.; et al.
Abstract : Introduction: The capacity of repetitive TMS to transiently interfere with cognitive processes in humans may offer an experimental platform for pharmacological studies. Developing compounds could then be tested to reverse artificially generated cognitive dysfunction, providing first hints of efficacy. In the FP7-IMI European 'Pharmacog' Project, an rTMS protocol previously published in the literature, was adapted and validated as a 'cognitive challenge model' to mimic episodic memory dysfunction occurring in early Alzheimer's disease. However, it would be desirable to test whether the effects of TMS are comparable and reproducible across different centres and time-point assessments. Objectives: Our main aims were, (1) to find out if visual memory interference through rTMS administration could be replicated using our specific experimental settings and task adaptations (Fig. 1), (2) to test if results are comparable in two centres and (3) to investigate if the effects obtained are reproducible when subjects are re-tested 15 days later. Methods: 68 healthy young male subjects were included. Neuronavigated (Fig. 1) repetitive TMS was applied over the left dorsolateral prefrontal cortex (LDLPFC) or the Vertex area (control condition) during encoding of pictures, for latter memory recognition. Subjects attended one of two research centres in three main occasions: On visit 1, rTMS was applied using a sham coil and served as a baseline measure. On visit 2, real rTMS was administered. On visit 3, 15 days later, a subsample ( N = 21) performed the same protocol to test for reproducibility of effects. Results: A time (visit 1 vs visit 2) × TMS type (LDLPFC vs Vertex) ANOVA and posterior pairwise comparisons revealed that only rTMS delivered over the LDLPFC and during visit 2 day resulted in a significant decrease in subsequent memory recognition ( F = 8.95, p = 0.004; Fig. 2a). No centre effect observed ( F = 0.03, p = 0.96). Initial rTMS effects could not be replicated in the subsample (Fig. 2b). Conclusions: Our findings offers positive evidence regarding the feasibility of adapting a rTMS cognitive interference protocol, to conduct new experimental research in separate independent institutions. The factors underlying the lack of test–retest reproducibility of the interference should be further investigated.